Yield persistence and evaluation of progenies and cultivars of the Lotus corniculatus L. - Caroso, Gilson F.; Paim, Nilton R.; Prates, Enio R. (Pesquisa Agropecuaria Brasileira, 2014)
Twenty-two progenies of the cv. São Gabriel, one line and six American cultivars of birdsfoot trefoil (Lotus corniculatus L.) were evaluated for yield, quality and persistence aspects, in a period from march of 1978 to may of 1979 at the Agricultural Experiment Station of the Federal University of Rio Grande do Sul, Guaíba, RS, Brazil. The following parameters were evaluated: average initial and final number of plants/m, mean percentage of the reduction in number of plants, mean rate of growth in heigth of the plants, in cm/week, average total dry matter yield in g/linear m, mean percentage of crude protein and mean percentage of "in vitro" digestibility of the dry matter. The analysis of variance showed statistical significance (P<0,05) for all paremeters evaluated. Some significant correlations were found between pairs of observations. The analysis of the covariance showed a negative and non-significant regression coefficient (b = - 0.24). (P>0,05), between initial number of plants and the total dry matter yield.